The roles of critical incidents to construct public senior high school english teachers’ identities development - Arima Renny Dayu Putri; Paulus Kuswandono (University of Kuningan, 2020)
This study investigated the role of critical incidents (CIs) to construct Public Senior High School English teachers’ identities development. The researchers examined the meanings of CIs and how these developed their identities as Public Senior High School English teachers. To gain the data, the researchers conducted Open-Form Questionnaire and Open-Ended Interview toward eight Public Senior High School English teachers in Yogyakarta. The data were collected using narrative inquiry statements which displayed respondents’ life story in constructing teachers’ identities related to their CIs. The result of this research demonstrated that there were 12 CIs which were classified into 3 major categories of CIs namely: students’ misbehavior, smart student, and self-improvement. The meanings of these CIs were; motivating teacher to be reflective teacher, empower teacher to be agentic teacher in finding solution, developing teachers’ identities, supporting teachers to have better quality of teaching, and improving teacher confidence. Those meanings of CIs gave a great role to construct Senior High School English teachers’ identity.